The metabolic syndrome - Després, Jean Pierre (Henry Stewart Talks, 2013)
Reaven’s syndrome X, Coronary heart disease (CHD) and type 2 diabetes odds ratio, Our "toxic" lifestyle, Landscape change in modifiable CVD risk factors, Risk of ischemic heart disease (IHD), Insulin resistance, The metabolic syndrome: distinctions of metabolic abnormalities, CHD risk, non-obese individuals, waist girth, abdominal obesity and management,- Liver fat and visceral fat: cardiometabolic risk link, Sex differences in liver fat content, Overall objectives of INSPIRE ME IAA, Categorization by T2D and tertiles of VAT, Triglyceride & HDL cholesterol concentrations in men & women, Inflammatory factors, liver fat, visceral adiposity & T2D, Frequency of prevalent CVD, Visceral obesity/ectopic fat screening tool, HyperTG waist survival and CHD risk study, Clinical diagnosis limitations, "Turbostatins”, The EPIC-Norfolk study, CHD event rate and physical activity, Reshaping lifestyle habits of obese patients